The Effect of Soft Tissue on Detecting Hip Impingement - Mahshid Yazdifar; Mohammadreza Yazdifar; Ebrahim Esat (European Scientific Journal, ESJ, 2017)
Hip impingement is a hip associated abnormality and it reduces the activity of those affected and also it can result in osteoarthritis. Current clinical methods in detecting hip impingement known as FADIR test. This is a manual method and relies heavily on surgeons experience and the method is prone to error. The use of computational programmes are known to be more accurate and reliable as the kinematic of contact can easily be studied using the digitised bones of the hip joint assuming that the impingement is determined by bone to bone contact kinematics. Current impingement studies assume that the kinematics of hip joint can be studied by assuming the centre of rotation is fixed for hip joint. For highly conforming joints this assumption is acceptable but for cases where conformity is poor the presence of soft tissue and soft tissue loading becomes very important. The important need in orthopaedics field is to develop a model without too much simplification. All previous work on detecting impingement has ignored the factor of soft tissue. In this paper for the first time the complete computational model of hip with soft tissue has been used to detect the impingement in a specific patient. In this paper the femur, acetabulum, cartilage and ligaments of specific patients were modelled in MIMICs using both MRI and CT scan. 3D hip models with and without soft tissues of normal hip, hip with impingement and hip with impingement after reshaping were modelled. The hip models were imported to detect impingement zone and impingement angle. Our results show that the soft tissue in hip model affects hip impingement angle and hip biomechanics. This finding also shows that, if the boundary condition is closer to the real hip, then the results of computer-aided program will be more reliable.